MEMBANGUN SEKOLAH UNGGUL BERORIENTASI KONSERVASI NILAI DAN WARISAN BUDAYA - Sutarto, Joko (Indonesian Journal of Conservation, 2012)
Globalization which is identified from the rapid growth of information and technology is suspected to bring impacts towards social dynamic and society culture. Communal values such as: manners, politeness, honesty, social solidarity, kinship, hospitality, mutual aid and nationalism which are used to be honored to unite and as the characteristics of Indonesian, now slowly degrading as pragmatism and materialism are getting stronger. When we adore global values, slowly but sure the true national identity is degradingor even vanished. The Conservation of values and cultural heritage through school teachings is fundamentally urgent to form studentsÃ¢â‚¬â„¢ character and capacity, the moral values of the students can be formed and internalized as a strong character if it is given as early as possible. This strategy is used to create superior schools aiming to preserve conservation values and cultural heritage such as the revitalization of the sublime values, character and national cultures through learning by prioritizing ethics, having the orientation to the conservation of values and cultural heritage, growing awareness, creating a dialogical school environment, developing the ability of learning how to learn. The role of teachers in the studying process and other activities around the school environment shall reflect a characteristics to be followed and taken as example for the students.Globalisasi yang ditandai kemajuan teknologi komunikasi dan informasi yang cepat dan merambah di semua lini kehidupan ditengarai membawa dampak terhadap dinamika sosial dan budaya masyarakat. Nilai-nilai Ã¢â‚¬Å“bebrayanÃ¢â‚¬Â seperti: Ã¢â‚¬Å“unggah ungguhÃ¢â‚¬Â, sopan santun, kejujuran, solidaritas sosial,Ã‚Â  kekeluargaan, keramahtamahan, gotong royong dan rasa cinta tanah air yang dulu dijunjung tinggi sekaligus kekuatanpemersatu dan merupakan karakteristik bangsa Indonesia, saat ini mengalami degradasi bersamaan dengan menguatnya nilai-nilai pragmatisme dan materialisme. Ketika kita lebih mengagung-agungkan nilai nilai global, maka lambat laun akan terjadi semakin menipis atau bahkan hilangnya jati diri bangsa. Konservasi nilai dan warisan budaya melaluiÃ‚Â  pembelajaran di sekolah dipandang sangat penting dalamrangka pembentukan watak dan kapasitas peserta didik, nilai moral pada diri peserta didik akan terbentuk dan terinternalisasi menjadi suatu karakter apabila ditanamkan sejak dini. Strategi yang digunakan untuk menciptakan sekolah unggul dengan orientasi konservasi nilai dan warisan budaya adalah revitalisasi nilai luhur, karakter dan budaya bangsa melalui pembelajaran dengan mengedepankan kaidah-kaidah etika, berorientasi konservasi nilai dan warisan budaya,penanaman kesadaran, penciptaan lingkungansekolah yang dialogis, mengembangkan kemampuan learning how to learn. peranan guru dalam proses pembelajaran dan kegiatan lain di lingkungan sekolah harus mencerminkan karakteristik yang dapat menjadi panutan dan teladan bagi peserta didik.